2018
DOI: 10.1001/jamaoto.2018.0987
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multimodal Analgesia Pathways in Outpatient Thyroid and Parathyroid Surgery and Association With Postoperative Opioid Prescription Patterns

Abstract: Adoption and adherence to the MMA protocol increased substantially over the study period for patients undergoing thyroid and parathyroid surgery and was associated with a simultaneous significant decline in prescription of postoperative opioid analgesics. Use of nonopioid multimodal agents, incorporating NSAIDs, was safe and did not lead to increased incidence of bleeding. Availability of effective nonopioid MMA pathways may favorably influence physician prescribing practices and avoid unnecessary opioid presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 15 publications
3
59
0
Order By: Relevance
“…Emerging studies support the use of multimodal analgesia following thyroid and parathyroid procedures. Militskah et al reported that it provides greater satisfaction scores than opioids alone . Shindo et al reported that multimodal analgesia reduced the total MME prescribed for both thyroidectomy (215 to 102) and parathyroidectomy (176 to 80) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Emerging studies support the use of multimodal analgesia following thyroid and parathyroid procedures. Militskah et al reported that it provides greater satisfaction scores than opioids alone . Shindo et al reported that multimodal analgesia reduced the total MME prescribed for both thyroidectomy (215 to 102) and parathyroidectomy (176 to 80) …”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies report multimodal analgesia to be effective in reducing opioid consumption and managing pain. These regimens commonly utilize acetaminophen staggered with a nonsteroidal anti‐inflammatory drug (NSAID)/cyclooxygenase‐2 (COX‐2) inhibitor and/or gabapentin . Concerns regarding increased risk of bleeding from NSAIDs/COX‐2 inhibitors have not been substantiated by studies thus far .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to this, many surgical subspecialties have tried to standardize prescribing practices and develop perioperative protocols for routine surgical procedures to guide prescribers. Otolaryngology has been no exception, and a quick review of the literature can find a number of articles reporting prescribing practices, alternate nonopioid regimens, and surveys of prescribers in all age groups and subspecialties . Despite this, there is no consensus on postoperative pain management for routine otolaryngology procedures.…”
Section: Introductionmentioning
confidence: 99%